Variability in Antarctic ozone loss in the last decade (2004–2013): high-resolution simulations compared to Aura MLS observations - Kuttippurath, Jayanarayanan; Godin-Beekmann, Sophie; Lefèvre, Franck; Santee, M. L.; Froidevaux, L.; Hauchecorne, Alain (Atmospheric Chemistry and Physics, 2015)
International audience A detailed analysis of the polar ozone loss processes during ten recent Antarctic winters is presented with high resolution Mimosa-Chim model simulations and high frequency polar vortex observations from the Aura Microwave Limb Sounder (MLS) instrument. Our model results for the Antarctic winters 2004–2013 show that chemical ozone loss starts in the edge region of the vortex at equivalent latitudes (EqLs) of 65–69° S in mid-June/July. The loss progresses with time at higher EqLs and intensifies during August–September over the range 400–600 K. The loss peaks in late September/early October, where all EqLs (65–83°) show similar loss and the maximum loss (>2 ppmv [parts per million by volume]) is found over a broad vertical range of 475–550 K. In the lower stratosphere, most winters show similar ozone loss and production rates. In general, at 500 K, the loss rates are about 2–3 ppbv sh−1 (parts per billion by volume/sunlit hour) in July and 4–5 ppbv sh−1 in August/mid-September, while they drop rapidly to zero by late September. In the middle stratosphere, the loss rates are about 3–5 ppbv sh−1 in July–August and October at 675 K. It is found that the Antarctic ozone hole (June–September) is controlled by the halogen cycles at about 90–95% (ClO–ClO, BrO–ClO, and ClO–O) and the loss above 700 K is dominated by the NOx cycle at about 70–75%. On average, the Mimosa-Chim simulations show that the very cold winters of 2005 and 2006 exhibit a maximum loss of ~3.5 ppmv around 550 K or about 149–173 DU over 350–850 K and the warmer winters of 2004, 2010, and 2012 show a loss of ~2.6 ppmv around 475–500 K or 131–154 DU over 350–850 K. The winters of 2007, 2008, and 2011 were moderately cold and thus both ozone loss and peak loss altitudes are between these two ranges (3 ppmv around 500 K or 150 ± 10 DU). The modeled ozone loss values are in reasonably good agreement with those estimated from Aura MLS measurements, but the model underestimates the observed ClO, largely due to the slower vertical ...